Bundle Theory, Teletransportation Paradox, and FourDimensionalist Approach - Turan Argun Sezer (Felsefe Arkivi)
The problem of “identity over time” is one of the most essential problems in the history of philosophy. However, the problem of identity arises not only with physical objects but also with the identity of consciousness itself. The problem of the identity of consciousness can be described as the question of whether it is a mere description or whether it has an ontological status as a being in itself. In this paper,I argue that the prominent theories of consciousness, such as the Bundle Theory, are insufficient for explaining problems, such as the transition of consciousness or split minds, by adapting the solutions of the four-dimensionalist approach to the transition of identity problems from the point of view of the philosophy of time. For this purpose, I cite examples from well-known puzzles of philosophy, namely the Ship of Theseus and Chisholm’s Coffee Cup, and apply the same examples to the transition of consciousness. Through the analogies of those examples, I argue for the temporal and half-temporal existence of consciousness. The main question here is whether there is a temporality of consciousness or an abstract ontological status of consciousness. In answering this question, I assume that consciousness, like any other spacetime object, has a mereological essence. I refute the Bundle Theory and Parfit’s solution by analogy with Sider’s argument against Perry and Prior. Thus, I enhance my argument in favor of the analytic metaphysics of identity.